2007
DOI: 10.1097/01.mlg.0000248737.65607.9e
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Herpes Simplex Virus Type 1 and Varicella‐Zoster Virus and Therapeutic Effects of Combination Therapy With Prednisolone and Valacyclovir in Patients With Bell's Palsy

Abstract: Reactivation of HSV-1 or VZV was observed in 34% of the patients with Bell's palsy. The effect of combination therapy with prednisolone and valacyclovir on recovery was not significantly higher than that with prednisolone alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
5
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 17 publications
3
89
5
2
Order By: Relevance
“…A escolha da abordagem terapêutica para a paralisia de Bell continua a ser um problema comum na prática médica [12][13][14][15][16][17]. Os resultados deste estudo relativamente à terapêutica antiviral estão de acordo com a revisão Cochrane de 2015 [18], que incluiu 11 ensaios controlados, com um total de 2883 pacientes com paralisia de Bell.…”
Section: Discussionunclassified
“…A escolha da abordagem terapêutica para a paralisia de Bell continua a ser um problema comum na prática médica [12][13][14][15][16][17]. Os resultados deste estudo relativamente à terapêutica antiviral estão de acordo com a revisão Cochrane de 2015 [18], que incluiu 11 ensaios controlados, com um total de 2883 pacientes com paralisia de Bell.…”
Section: Discussionunclassified
“…6 The second study (296 recruited) reported a positive outcome, 7 but this result was compromised by a number of serious methodological flaws, including an inadequate randomisation procedure, single blind design, and a 25% drop out rate (not included in the analyses). 8 Following the publication of these three trials in 2007, 4,6,7 some commentators still recommended the use valaciclovir for those with severe facial weakness, 9,10 despite the evidence of lack of effectiveness. Most recently, the Swedish study 5 has hopefully put the matter beyond doubt, with no evidence that valaciclovir was effective in the management of Bell's palsy.…”
Section: Doi: 103399/bjgp09x453756mentioning
confidence: 99%
“…Serological studies were carried out in the two Japanese studies and revealed evidence of varicella zoster reactivation in 23/296 (8%) 7 and 28/150 (19%). 6 The latter study also measured HSV serology which indicated reactivation in 29/150 (19%). 6 Antiviral enthusiasts suggest that because the dose of aciclovir used in the Scottish trial 4 was insufficient to treat varicella zoster and because patients were not tested serologically, unwitting inclusion of varicella zoster patients may have biased the study, producing an erroneous negative result.…”
Section: Doi: 103399/bjgp09x453756mentioning
confidence: 99%
See 2 more Smart Citations